Empowerment Strategies for the Poor Based on Spatial Patterns in Tapin Regency - Safitri, Evi Selvi Adriani Dewi; Fitriyadi, Fitriyadi; Hidayat, Yusuf (International Journal of Multidisciplinary Approach Research and Science, 2024)
This research aims to analyze whether education, health, unemployment, asset ownership, and road infrastructure factors simultaneously influence the spatial patterns of poverty in Tapin Regency. The final results will determine strategies for empowering the poor in Tapin Regency. This study employs a quantitative approach with statistical techniques and follows a descriptive correlational design. The results show that education, health, unemployment, asset ownership, and road infrastructure variables have a significant partial and simultaneous impact on poverty in both the three sub-districts and Tapin Regency as a whole. The primary strategy for empowering the poor in Tapin Regency is the Strength-Opportunity (S-O) strategy. This involves enhancing the role of companies through Corporate Social Responsibility (CSR) programs aimed at empowering the poor by developing superior commodity products and increasing the number of local entrepreneurs as part of the local government's priority strategy to reduce poverty. The recommendations for the Tapin Regency Government to empower the poor economically include improving the education and health levels of the community, partly by providing infrastructure to facilitate access to educational and health facilities, reducing unemployment through increased labor-intensive programs, and constructing road infrastructure to alleviate the isolation of areas prone to poverty.